Hepatitis B seroprevalence in the U.S. military and its impact on potential screening strategies. Issue 9 (10th July 2020) - Scott, Paul T; Cohen, Robert L; Brett-Major, David M; Hakre, Shilpa; Malia, Jennifer A; Okulicz, Jason F; Beckett, Charmagne G; Blaylock, Jason M; Forgione, Michael A; Harrison, Stephen A; Murray, Clinton K; Rentas, Francisco J; et al.
Abstract: Introduction: Knowledge of the contemporary epidemiology of hepatitis B virus (HBV) infection among military personnel can inform potential Department of Defense (DoD) screening policy and infection and disease control strategies. Materials and Methods: HBV infection status at accession and following deployment was determined by evaluating reposed serum from 10, 000 service members recently deployed to combat operations in Iraq and Afghanistan in the period from 2007 to 2010. A cost model was developed from the perspective of the Department of Defense for a program to integrate HBV infection screening of applicants for military service into the existing screening program of screening new accessions for vaccine-preventable infections. Results: The prevalence of chronic HBV infection at accession was 2.3/1, 000 (95% CI: 1.4, 3.2); most cases (16/21, 76%) identified after deployment were present at accession. There were 110 military service-related HBV infections identified. Screening accessions who are identified as HBV susceptible with HBV surface antigen followed by HBV surface antigen neutralization for confirmation offered no cost advantage over not screening and resulted in a net annual increase in cost of $5.78 million. However, screening would exclude as many as 514 HBV cases each year from accession. Conclusions: Screening for HBV infection at service entry would potentially reduce chronic HBV infection in the force, decrease the threat of transfusion-transmitted HBV infection in the battlefield blood supply, and lead to earlier diagnosis and linkage to care; however, applicant screening is not cost saving. Service-related incident infections indicate a durable threat, the need for improved laboratory-based surveillance tools, and mandate review of immunization policy and practice.